The anti‐infection drug furazolidone inhibits NF‐κB signaling and induces cell apoptosis in small cell lung cancer - Jin‐Guo Yu; Cheng‐Hong Ji; Min‐Hua Shi (Kaohsiung Journal of Medical Sciences, 2020)
Abstract Targeting nuclear factor kappa B (NF‐κB) signaling pathway has become a promising strategy for the development of new antitumor drugs. In this paper, we found that anti‐infection drug furazolidone (FZD) could significantly inhibit NF‐κB‐driven luciferase activity, and FZD could markedly inhibit both of the constitutive and tumor necrosis factor‐α (TNFα)‐triggered phosphorylation of NF‐κB p65 in small cell lung cancer (SCLC). Further studies revealed that FZD inhibited the expression of inhibitor of kappa B kinase β (IKKβ) in SCLC cells. In addition, we found that FZD had significant antitumor activities in SCLC cells. FZD could markedly suppress the cell viability of SCLC cells dose‐dependently, and FZD could significantly induce the cleavages of poly ADP‐ribose polymerase (PARP) and Caspase3, the biomarkers of cell apoptosis, in SCLC cells. The flow cytometry also revealed that FZD induced cell apoptosis in SCLC cells. Finally, we also found that overexpression of constitutively activated IKKβ could significantly abolish FZD‐induced cell growth inhibition in SCLC cells, which further confirmed that FZD displayed its anti‐SCLC activity through regulating NF‐κB signaling pathway.